Letter to Malibu Residents - Stop LNG - California Coastal Protection Network (California Coastal Protection Network)
Letter to Malibu residents from CCPN to inform them the potential negative environmental effects LNG terminal can do if implemented. Informs residents of public forums they can attend to voice any concerns.